Design andSynthesis of Coumarin-Functionalized Zn(II)Phthalocyanine: DFT Analysis, Photophysical, and Photodiode Properties - Kazancicok, Zehra; Cetiner, Rumeysa; Ozdemir, Mucahit; Koksoy, Baybars; Biryan, Fatih; Salan, Umit; Koran, Kenan (Amer Chemical Soc, 2026)
In this study, a novel phthalonitrile derivative (2) bearing a coumarin side group and its corresponding Zn(II) phthalocyanine complex (3) were successfully synthesized and structurally characterized using FT-IR, NMR, UV-vis, MALDI-TOF MS, and X-ray crystallography. Optical studies revealed that ZnPc (3) exhibits characteristic Q-band absorption in the visible region along with fluorescence emission, indicating its suitability for photonic applications. DFT calculations showed a significant reduction in the HOMO-LUMO gap from compound 1 to compound 3, with ZnPc (3) displaying the lowest band gap (2.16 eV), strong pi-conjugation, and pronounced intramolecular charge transfer (ICT). MEP analysis further confirmed enhanced charge separation and donor-acceptor character. Electrochemical results supported these findings, revealing improved electron transfer and a narrow band gap (1.64 eV) for ZnPc (3). Al/p-Si/compound 2/Al and Al/p-Si/ZnPc 3/Al Schottky diodes exhibited rectifying behavior; however, ZnPc (3) showed superior performance with higher barrier height (0.68 eV), lower ideality factor (3.20), and higher rectification ratio (RR = 1702). Moreover, the increasing photocurrent under reverse bias with illumination confirmed that ZnPc acts as an efficient photoactive material. Overall, the results demonstrate that the ZnPc derivative, owing to its favorable electronic structure, strong ICT behavior, and enhanced charge transport properties, is a promising candidate for photodiode and optoelectronic applications.
Keywords: Phthalocyanines; Photosensitizers; Exchange; Series; Dyes